Plague Image and Imagination from Medieval to Modern Times
XIX, 298 p. 34 illus.
Keywords: “This book offers an original, multidisciplinary approach to the global history of pandemics, focusing on the making and circulation of visual images. It will interest specialists in medical humanities, visual studies, history of disease, history and theory of photography, visual anthropology, science and technology studies, and medical sociology.” - Jennifer Tucker, Associate Professor of History, Wesleyan University, USA This edited collection brings together new research by world-leading historians and anthropologists to examine the interaction between images of plague in different temporal and spatial contexts, and the imagination of the disease from the Middle Ages to today. The chapters in this book illuminate to what extent the image of plague has not simply reflected, but also impacted the way in which the disease is experienced in different historical periods. The book asks what is the contribution of the entanglement between epidemic image and imagination to the persistence of plague as a category of human suffering across so many centuries, in spite of profound shifts in our medical understanding of the disease. What is it that makes plague such a visually charismatic subject? And why is the medical, religious and lay imagination of plague so consistently determined by the visual register? In answering these questions, this volume takes the study of plague images beyond its usual, art-historical framework, so as to examine them and their relation to the imagination of plague from medical, historical, visual anthropological, and postcolonial perspectives.